Landscape and Contemporary Art: Overlap, Disregard, and Relevance - Kingery-Page, Katie (My University, 2011)
Landscape, viewed for centuries by the art world as either an inspirational source for art or as a kind of decorative art, emerged with a new prominence during the twentieth century. Artists and landscape architects now share a realm of overlapping practice. By understanding contemporary art as a body of knowledge and art itself as a ‘mode of knowledge,’ students, educators, and practitioners of landscape architecture can compete more effectively with other ‘form-givers’ in 21st century culture. Art as a mode of knowledge is often disregarded within landscape architecture, in favor of seemingly more analytical approaches to design research dilemmas. Using examples of 20th and 21st century urban art, I argue for art as a mode of knowledge relevant to current landscape architecture practices. I demonstrate the results of applying normative artistic research to a student design project.
Keywords: Landscape architecture; Contemporary art; Urban art; Hip hop; Bronx; Detroit; New Orleans